Identifikasi Faktor yang Mempengaruhi Partisipasi Masyarakat dalam Pengelolaan Bank Sampah - Dinda Audina; Lely Syiddatul Akliyah (UNISBA Press, 2023)
Abstract. The waste bank management is one of the work programs in Cipamokolan Village as a form of effort in carrying out household-scale waste management. However, not all residents of each RW in Cipamokolan Village have participated in waste management efforts through waste bank management activities. The purpose of this study is to identify what factors that affecting community participation in waste bank management in Cipamokolan Village. The approach method used in this study is a quantitative method with the Guttman scale analysis method and multiple linear regression analysis. Based on the results of the study, it was found that community participation with the status of members in the planning stage of waste bank activities in Cipamokolan Village was classified into the high participation category with a percentage of 68%, while non-members were classified as moderate participation with a percentage of 49%. Furthermore, the participation of the community with the status of members in the stage of implementing waste bank activities in Cipamokolan Village is classified into the high participation category with a percentage of 75.6%, while non-members are classified as moderate participation with a percentage of 37%. There were also 3 factors that influenced community participation in this study, namely land availability variables, environmental/people influence variables, and communication effectiveness variables. Therefore, the management of the waste bank must strive for socialization and community empowerment so that they can participate in managing the waste bank. Therefore, the management of the waste bank must strive for socialization and community empowerment so that they can participate in managing the waste bank. Abstrak. Pengelolaan bank sampah menjadi salah satu program kerja di Kelurahan Cipamokolan sebagai salah satu bentuk upaya dalam melaksanakan pengelolaan sampah skala rumah tangga. Namun, belum semua warga tiap RW di Kelurahan Cipamokolan yang ikut serta dalam upaya pengelolaan sampah melalui kegiatan pengelolaan bank sampah. Adapun tujuan dari penelitian ini ialah untuk mengidentifikasi faktor apa saja yang mempengaruhi partisipasi masyarakat dalam pengelolaan Bank Sampah di Kelurahan Cipamokolan. Metode pendekatan yang digunakan pada penelitian ini ialah metode kuantitatif dengan metode analisis skala Guttman dan analisis regresi linear berganda. Berdasarkan hasil penelitian, diperoleh bahwa partisipasi masyarakat yang berstatus sebagai anggota dalam tahap perencanaan kegiatan bank sampah di Kelurahan Cipamokolan ini tergolong ke dalam kategori partisipasi tinggi dengan persentase sebesar 68%, sedangkan untuk non anggota tergolong kedalam partisipasi sedang dengan persentase sebesar 49%. Selanjutnya, partisipasi masyarakat yang berstatus sebagai anggota dalam tahap pelaksanaan kegiatan bank sampah di Kelurahan Cipamokolan ini tergolong ke dalam kategori partisipasi tinggi dengan persentase sebesar 75,6%, sedangkan untuk non anggota tergolong kedalam partisipasi sedang dengan persentase sebesar 37%. Ditemukan juga 3 faktor yang mempengaruhi partisipasi masyarakat pada penelitian ini, yaitu variabel ketersediaan lahan, variabel pengaruh lingkungan/orang sekitar, dan variabel efektivitas komunikasi. Oleh karena itu, pihak pengelola bank sampah harus mengupayakan sosialisasi dan pemberdayaan masyarakat agar turut berpartisipasi dalam pengelolaan bank sampah.